CLIMA ORGANIZACIONAL EN EL DEPARTAMENTO DE BIENES E INVENTARIOS DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO - Diaz Aguirre, Wendy Melissa (2018)
The Technical University of Babahoyo whose abbreviations are UTB, is an Institution of Higher Education, created on October 5, 1971 by decree by the then President of the Republic of Ecuador, Dr. José María Velasco Ibarra with 2 faculties: Education Sciences and Agricultural Engineering and veterinary medicine. Currently the UTB has the following careers to follow: Faculty of Legal, Social Sciences and Education, Faculty of Administration, Finance and Information Technology, Faculty of Agricultural Sciences and Faculty of Health Sciences.